Conception and development of Sexual Health indicators to advance the quality of spinal cord injury rehabilitation: SCI-High Project. (30th September 2019) - Elliott, Stacy; Jeyathevan, Gaya; Hocaloski, Shea; O'Connell, Colleen; Gulasingam, Sivakumar; Mills, Sandra; Farahani, Farnoosh; Kaiser, Anita; Mohammad Alavinia, S.; Omidvar, Maryam; Craven, B. Catharine
Abstract : Context: Although spinal cord injury or disease (SCI/D) results in complex biological and psychosocial impairments that adversely impact an individual's overall quality of sexual life, sexual health is poorly integrated into the current rehabilitation processes. Therefore, it is vital to promote sexual health as a rehabilitation priority. Herein, we describe the selection of Sexual Health structure, process and outcome indicators for adults with SCI/D in the first 18 months after rehabilitation admission. Methods: Experts in sexual health and the SCI-High team identified key factors that influence the sexual health outcomes of rehabilitation interventions to inform Driver diagram development. This diagram informed the selection and development of indicators to promote a permissive environment for discussion of sexual health issues among regulated health care professionals (HCPs). A review of literature and psychometric properties of measurement tools facilitated final indicators selection. Results: The structure indicator is the proportion of rehabilitation HCPs who have completed annual preliminary sexual health training. The process indicator is the proportion of SCI/D inpatients that have a documented introduction to available local sexual health resources. The outcome indicator is a sexual health patient questionnaire used to assess sexual health patient outcomes and sexual health information/educational needs. Rapid-cycle piloting verified that the indicator tools developed are feasible for implementation. Conclusion: Successful implementation of the Sexual Health structure, process and outcome indicators will promote a permissive environment to enable open discussion, and lead to provision of equitable and optimal care related to sexual health following SCI/D. This will ultimately advance sexual health rehabilitation across the nation.